1996
DOI: 10.1021/jm9505829
|View full text |Cite
|
Sign up to set email alerts
|

Ionophore Properties of Monensin Derivatives Studied on Human Erythrocytes by 23Na NMR and K+ and H+ Potentiometry:  Relationship with Antimicrobial and Antimalarial Activities

Abstract: Eight derivatives of monensin with a modified C25-C26 moiety were synthesized. Their ionophore properties were studied on human erythrocytes by measuring Na+ influx with 23Na NMR and concomitant K+ and H+ efflux by potentiometry. Modification of OH-26 led to inversion of selectivity of transport in favor of K+/Na+ in comparison with monensin. This selectivity disappeared by suppression of the C26-OH moiety. Finally the ionophore ability was lost if the head-to-tail chelation of the monensin skeleton was preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 36 publications
(95 reference statements)
0
18
0
2
Order By: Relevance
“…Notably, monensin has potent in vitro and in vivo antimalarial activity [60,61]. Eight derivatives of monensin showed potential antimalarial properties in the nanomolar range when tested in vitro against Plasmodium falciparum [62]. The antimalarial effect may be partially due to accelerated suicidal death and clearance of parasitized erythrocytes [63].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, monensin has potent in vitro and in vivo antimalarial activity [60,61]. Eight derivatives of monensin showed potential antimalarial properties in the nanomolar range when tested in vitro against Plasmodium falciparum [62]. The antimalarial effect may be partially due to accelerated suicidal death and clearance of parasitized erythrocytes [63].…”
Section: Discussionmentioning
confidence: 99%
“…Rochdi etal. [63] have demonstrated that 2d and 2e monensin derivatives cause an increase in the effective transport of potassium cation through the membrane, whereas there is a decrease in the transport of sodium cations. Thus, these derivatives preferentially complex and transport potassium cations prior to sodium cations.…”
Section: Monensin a Derivatives And Their Antimicrobial Activitymentioning
confidence: 99%
“…Monensin activity against the blood stage of P. falciparum has been described in vitro with IC50 of 1.1 nM (Adovelande and Schrevel, 1996), 1.4 nM (Gibot et al, 1999), 2.1 nM (Gumila et al, 1997) and 2.3 nM, (Rochdi et al, 1996). A recent screening of drugs predicted by molecular topology has also found monensin inhibitory activity against the liver stage of P. yoelii and P. falciparum in vitro (Mahmoudi et al, 2008).…”
Section: Inhibition Of Liver Infection In Mice By a Single Injection mentioning
confidence: 99%